Malaysia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the analysis of the IMF's projections and estimates for Malaysia on gross domestic product by expenditures and production at constant 1987 prices and at current prices; industrial production index; labor market developments; consumer and producer price indices; federal government revenue and grants; economic and functional classification of federal government expenditure and net lending; federal government operations and fiscal operations; operations of statutory bodies, state, and local governments; general government operations; monetary survey; banking survey; international reserves; balance of payments; interbank swap transactions; developments in Malaysian exchanges during 1996-2000, and so on.